PENINGKATAN HASIL BELAJAR IPS MENGGUNAKAN VIDEO ANIMASI BERGERAK BERBASIS PBL DI SD - Irmawati D Ishak; Paramita Tahalu (LPPM Universitas Muhammadiyah Gorontalo, 2021)
The purpose of this study was to improve student learning outcomes in social studies using animated video moves based on the Problem Based Learning Model in Class V SDN 3 Mootilango, Gorontalo District. With the formulation of the problem whether the use of Problem Based Learning-based animated video can improve student learning outcomes in class V social studies subjects at SDN 3 Mootilango, Gorontalo District. Research subjects in Classroom Action Research (PTK) were students of class V with a total of 13 students consisting of 10 male students and 3 female students. And the main target in this study is to improve student learning outcomes in social studies subjects. The results of this study indicate an increase in the ability of students in completing assignments and evaluation questions both at each meeting and each cycle. This is shown in the learning outcomes of students who achieved learning completeness in the first cycle of learning completeness reached 62%, and at the second meeting it reached 77% and at the third meeting it increased to 93%. And it has exceeded the expected performance indicators.Tujuan Penelitian ini adalah meningkatkan hasil belajar siswa pada mata pelajaran IPS menggunakan Video animasi bergerak bebasis Model Problem Based Learning di Kelas V SDN 3 Mootilango Kabupaten Gorontalo. Dengan Rumusan masalah Apakah dengan penggunaan Video animasi bergerak berbasis Problem Based Learning dapat meningkatkan hasil belajar siswa pada mata pelajaran IPS kelas V di SDN 3 Mootilango Kabupaten Gorontalo. Subjek Penelitian pada Penelitian Tindakan Kelas (PTK) ini adalah siswa kelas V dengan jumlah siswa 13 yang terdiri dari 10 siswa laki-laki dan 3 siswa Perempuan. Dan sasaran utama dalam penelitian ini adalah meningkatkan hasil belajar siswa pada mata pelajaran IPS. Hasil Penelitian ini menunjukan peningkatan kemampuan siswa dalam menyelesaikan Tugas maupun Soal Evaluasi baik setiap Pertemuan maupun setiap Siklus. Hal ini di tunjukan pada hasil belajar siswa yang mencapai ketuntasan belajar pada siklus I meningkat menjadi 77% dan pada siklus II mengalami peningkatan yang sangat signifikan yaitu mencapai 93%. Dan sudah melampaui indikator kinerja yang di harapkan.